Anti-Corruption Education and the Strengthening of Students’ Moral Awareness: The Role of School Culture and Teacher Modeling - Randy, Randy Saputra; Nur, Jumiati; Rismawati, Rismawati (State Islamic University of Palopo, 2026)
This study aims to analyze the implementation of anti-corruption education in strengthening students’ moral awareness at SMAN 3 Pangkep. This research is motivated by the importance of character education and integrity development among students amid the persistence of corruption-related behavior in society. Previous studies have generally focused on the conceptual integration of anti-corruption values in learning, while limited studies have explored the role of school culture, teacher role modeling, and contextual habituation in strengthening students’ moral awareness. This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving principals, teachers, and students as informants. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checking. The findings reveal that anti-corruption education at SMAN 3 Pangkep is implemented through the integration of anti-corruption values into Civic Education learning, school culture, and teacher role modeling. The study identified the development of students’ moral awareness related to honesty, responsibility, discipline, and fairness through contextual learning experiences and daily habituation practices. However, several students still demonstrated inconsistent behavior regarding discipline and academic honesty, indicating that moral awareness formation is a continuous process requiring sustainable reinforcement. This study concludes that anti-corruption education contributes positively to strengthening students’ moral awareness when supported by contextual learning, integrity-based school culture, and consistent teacher role modeling. The findings imply the importance of collaborative and sustainable character education practices in developing students’ integrity within school environments.